Proyecto de factibilidad para la creación de una empresa de producción de ropa deportiva Jordan textiles en la ciudad de Cariamanga cantón Calvas de la provincia de Loja para el año 2016 - Díaz Cueva, Jonathan Alfonso (2017)
This research work is of great importance since it was developed with the purpose of determining the commercial viability of the proposal to create a company producing sportswear in the Canton Calvas and this way contribute to the socioeconomic development of the locality, generating sources of Direct and indirect employment, improving the economy of their homes and the sector in general. This project was taken into account because this site is expected to have an attractive market for the commercialization of this type of clothing, in addition to that the city lacks a company dedicated to the elaboration of this type of garments. In order to deal with the present theme, the following methods were used: scientific, inductive, deductive, analytical, which allowed to determine the existing problems in the environment, as well as the investment opportunities thanks to resources and demand exist in the locality, Technique of the same survey that was applied to a representative sample of the population which is calculated in 388 surveys that allowed me to carry out the market study in order to determine who will be the potential consumers of our product. It began with the Market Study for this purpose were applied 388 surveys to the population of Canton Calvas; In order to know the level of acceptance of the product additionally for the study of the supply was surveyed to 4 supplier of textile products based on the information obtained was determined an unsatisfied demand of 35.345 sports suits for the first year of project execution Next, the technical study was developed, which allowed to determine the optimal location of the plant, which will be located in the Cariamanga parish of Canton Calvas, it was established that the installed capacity of the company is 3,840 sports suits per year, will begin to produce To 80% of its installed capacity, this is 3,072 sports suits in its first year of operation. The process diagram was developed for the production of sports suits, from the preparation of the materials for the preparation to the packing and storage of the finished product; We analyzed the requirements for the operation of the company, such as machinery, tools, furniture, especially the raw material needed for the production of the product. In the engineering of the project, the physical infrastructure and the distribution of the plant were designed, in which all the departments of the company that have an overall measure of 106m2 are built. In the administrative study it was determined that the company is constituted as a Limited Company, with the name of: Jordán Textiles, which consists of three partners who will have the same number of shares each. It was also determined the need to have 9 people to start the project. The Administrative structure was elaborated which consists of the structural, functional and positional organizational charts; For each of the positions the function manual was developed. The economic study determined that for the implementation of the project an investment of USD $ 43.502.64 of the United States of America is required, which will be financed 75.00% by equity and the remaining 25.00% by means of an institution With an interest rate of 13.58%. The cost of production for the first year is USD $ 67,575,44 United States dollars, with a sales income of USD $ 92.405,76 from the United States of America. Which allows generating a net profit of USD $ 14.816,25 United States of America? A cash flow of US $ 11,937,91 is also calculated. In making the financial evaluation it was possible to determine that after having recovered the investment will have a benefit of USD $ 12,332.43 United States of America; The period of capital recovery is 4 years, 3 months and 11 days; The financial indicators determined that the Net Present Value is $ 57.050,32; The ratio (Profit / Cost) is 1.20; The Internal Rate of Return is 29,99%; And the Sensitivity Analysis in the increase of the costs is of 4% and in the reduction of the income is of 2%. Finally they arrived at the conclusions and recommendations in which it is due to form the present study. The present study, becomes a profitable project, with good market expectations; In addition to contributing to strengthen the economy of the area, generate jobs, raise the economic level of the population and thus improve their quality of life.